MENGURAI INGATAN KOLEKTIF BERSAMA MAURICE HALBWACHS, JAN ASSMANN DAN ALEIDA ASSMANN Dalam Konteks Peristiwa 65 di Indonesia - Reza A.A Wattimena (Litbang STFT Widya Sasana Malang, 2016)
Remembering is a social action. It assumes the existence of certain social context as a background. It uses also language and various symbols which also a product of collectivity. Memory is also the foundation of identity in both personal and social levels. Collective self image of a society is formed by its collective memory and interpretation of events in the past. However, with the development of information and communication technology, collective memory experiences crisis. It changes to a mere technical information without meaning. This does not change the importance of collective memory. In Indonesian context, collective memory plays a very important role as the foundation of reconciliation in the context of 1965 events.This article is inspired by Maurice Halbwachs, Jan Assmann and Aleida Assmann.